Menumbuhkan Nasionalisme melalui Inovasi Game Pada Peringatan Hari Kemerdekaan di Sekolah SMA Nurul Jadid - Ibnu Syarofi; Mohammad Sofyan Adi Pranata (Lentera Salam Institute, 2026)
Nationalism among Generation Z students faces challenges from globalization and foreign cultural influences that overshadow national identity. This community service aimed to foster nationalism through innovative educational games during Independence Day celebrations at SMA Nurul Jadid. The activity involved 180 female students from grades X, XI, and XII through a participatory and collaborative approach in four stages: preparation, development, implementation, and evaluation. Three types of educational games were developed: Interactive Quiz on Independence History, Role Playing Game "Journey to Independence", and Collaborative Puzzle Game "Assembling Independent Indonesia". Implementation was conducted on August 16-17, 2024, with students divided into 36 groups participating in game rotation systems. Evaluation through pre-test and post-test showed a significant increase in knowledge of 34.95% with p-value < 0.001. Perception questionnaires revealed that 88.89% of students felt increased pride as Indonesian citizens and 96.67% desired similar activities in the future. The innovation successfully demonstrated that digital technology can be integrated with Islamic values and pesantren traditions without contradiction, while creating meaningful learning experiences that effectively instill nationalism values among digital native generation students.